Evaluation of Strategies and Implementation of Starbucks Coffee to Establish The Image of Indonesian Coffee - Sri Ayu Maharani; Isabella Astrid Siahaya (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
This study discusses the strategy of communication and implementation used by Starbucks Coffee Indonesia to establish the image of Indonesian coffee. Concepts and theories used in this study are the image and the four planning work program based on Cutlip, Centre & Broom in Defining the problem or opportunity, Strategy, Implementation and the last is evaluation program. The method used in this research is the qualitative method with in-depth interviews, observation, and documentation. The established wish image of Indonesian coffee is Indonesian rich in diverse types of coffee. From this study, it was found that Starbucks Coffee does not have a strategy and specific implementation in shaping the image of Indonesian coffee. Strategy and implementation used to establish the image of Indonesian coffee are the same with the strategy and implementation which is used for other coffee in Starbucks. There is no special treatment for established the image of Indonesian Coffee, although Starbucks coffee has always adjusted the value of wherever Starbucks located. Besides, Starbucks Coffee never performs an evaluation to measure the success of the program. From these activities can be seen that there are some customers who already know about the image which is established by Starbucks, while others people simply know that Starbucks sells coffee from Indonesia. As a recommendation, Starbucks should have a strategy and specific implementation to establish the image of Indonesian coffee.